Nurses’ Perceived Barriers to The Prevention of Pressure Injury and Related Factors in Indonesia - Yunita Sari; Arif Setyo Upoyo; Annas Sumeru; Wastu Adi Mulyono; Akhyarul Anam (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2023)
Background. Incidence of pressure injury (PI) in Indonesia is high. Therefore, Indonesian nurses should take measures to prevent PI from developing. Considering the high incidence of PI in Indonesia, there could be some barriers faced by Indonesian nurses in performing prevention of PI. However, to date, no study has assessed the perceived barriers and factors associated with perceived barrier of prevention of PI in Indonesian nurses. Therefore, this study aimed to assess perceived barriers to prevention of PI and associated factors in Indonesian nurses. Methods. A total of 521 nurses participated in the study. A pressure injury prevention barriers questionnaire was used to assess perceived barriers of prevention of PI. A multivariate logistic regression model was used to analyse factors associated with the perceived barriers. Results. The two most commonly perceived barriers in nurses were lack of preventive devices such as special mattresses, cushions, and skin care products, and a lack of training courses related to prevention of PI. Associated factors emerging from the results were working experience (AOR =1.74) and working unit (AOR =2.73).